"Und dann war das auch noch so ein kleines, zartes Persönchen": Grundschullehrkräfte im Entscheidungsdilemma zwischen Fördern und Selektieren - Miller, Susanne; Kottmann, Brigitte (Diagnostik im Kontext inklusive Bildung)

Selektion inklusive?! Widersprüche bei der umsetzung von Inklusion in der Schule - Kottmann, Brigitte; Miller, Susanne (Empirische Forschung im Kontext Schule)

Bildung und Hochschule. Impulse für Studium und Lehre am Beispiel des Leuphana College.

Integrative Verknüpfung von Studium und Praxis am Leuphana College. - Hellmann, Karina; Teigeler, Mareike; Seifert, Andreas (Bildung und Hochschule. Impulse für Studium und Lehre am Beispiel des Leuphana College.)

“Und sie bewegt sich doch!” – Wie spezifische Lerngelegenheiten die bildungswissenschaftlichen Kompetenzen von Lehramtsstudierenden fördern können. - Plöger, Wilfried; Scholl, Daniel; Seifert, Andreas (Zeitschrift für Pädagogik)

Universitäre Bildung und Hochschule im Wandel – das Beispiel Leuphana Universität Lüneburg. - Schütz, Julia; Seifert, Andreas; Gunkel, Marjaana (Das Hochschulwesen)

Smale-Scale-Assessments in den Bildungswissenschaften. - Lüders, Manfred; Seifert, Andreas (Lehrerbildung auf dem Prüfstand)

Preschoolers’ engagement in social interaction with an autonomous robotic system. - Lücking, Philipp; Rohlfing, Katharina; Wrede, Britta; Schilling, Malte (Proceedings of the IEEE ICDL-EpiRob 2016)

Vocal interactions at the dawn of communication: The emergence of mutuality and complementarity in mother-infant interaction. - Leonardi, Giuseppe; Nomikou, Iris; Rohlfing, Katharina; Rączaszek-Leonardi, Joanna (Proceedings of the IEEE ICDL-EpiRob 2016)

Pragmatic Frames for Teaching and Learning in Human–Robot Interaction: Review and Challenges - Vollmer, Anna-Lisa; Wrede, Britta; Rohlfing, Katharina; Oudeyer, Pierre-Yves (Frontiers in Neurorobotics)

Language meddles with infants‘ processing of observed actions - Sciutti, Alessandra; Lohan, Katrin Solveig; Gredebäck, Gustaf; Koch, Benjamin; Rohlfing, Katharina (Frontiers in Robotics and AI)

Language—at all times. Action and interaction as contexts for enriching representations. - Nomikou, Iris; Malte, Schilling; Heller, Vivien; Rohlfing, Katharina (Interaction Studies)

Die KOMFOR-Studie zum studentischen Wahlverhalten in überfachlichen Studienprogrammen – statistische Analysen und Auswertung von Interviews. - Strunz, Cathleen; Adomßent, Maik; Seifert, Andreas; Schütz, Julia; Gunkel, Marjaana (Bildung und Hochschule. Impulse für Studium und Lehre am Beispiel des Leuphana College.)

Embodied Language Learning and Cognitive Bootstrapping: Methods and Design Principles - Lyon, Caroline; Nehaniv, Chrystopher L.; Saunders, Joe; Belpaeme, Tony; Bisio, Ambra; Fischer, Kerstin; Forster, Frank; Lehmann, Hagen; Metta, Giorgio; Mohan, Vishwanathan; Morse, Anthony; Nolfi, Stefano; et al. (International Journal of Advanced Robotic Systems)
Co-development of action, conceptualization and social interaction mutually scaffold and support each other within a virtuous feedback cycle in the development of human language in children. Within this framework, the purpose of this article is to bring together diverse but complementary accounts of research methods that jointly contribute to our understanding of cognitive development and in particular, language acquisition in robots. Thus, we include research pertaining to developmental robotics, cognitive science, psychology, linguistics and neuroscience, as well as practical computer science and engineering. The different studies are not at this stage all connected into a cohesive whole; rather, they are presented to illuminate the need for multiple different approaches that complement each other in the pursuit of understanding cognitive development in robots. Extensive experiments involving the humanoid robot iCub are reported, while human learning relevant to developmental robotics has also contributed useful results. Disparate approaches are brought together via common underlying design principles. Without claiming to model human language acquisition directly, we are nonetheless inspired by analogous development in humans and consequently, our investigations include the parallel co-development of action, conceptualization and social interaction. Though these different approaches need to ultimately be integrated into a coherent, unified body of knowledge, progress is currently also being made by pursuing individual methods.
Keywords: Robot Language; Human Robot Interaction; HRI; Developmental Robotics; Cognitive Bootstrapping; Statistical Learning

Effekte von Objekt-Familiarisierung auf die frühe gestische Kommunikation. Individuelle Unterschiede in Hinblick auf den späteren Wortschatz - Grimminger, Angela; Lüke, Carina; Ritterfeld, Ute; Liszkowski, Ulf; Rohlfing, Katharina (Frühe Bildung)
There is ongoing discussion on the function of the early production of gestures with regard to whether they reduce children's cognitive demands and free their capacity to perform other tasks (e.g., Goldin-Meadow & Wagner, 2005) or whether young children point in order to share their interest or to elicit information from their caregivers (e.g., Begus & Southgate, 2012; Liszkowski, Carpenter, Henning, Striano & Tomasello, 2004). The different assumptions lead to diverse predictions regarding infants' gestural or multimodal behavior in recurring situations, in which some objects are familiar and others are unfamiliar. To examine these different predictions, we observed 14 children aged between 14 and 16 months biweekly in a semi-experimental situation with a caregiver and explored how children's verbal and gestural behaviors change as a function of their familiarization with objects. We split the children into two groups based on their reported vocabulary size at 21 months of age (larger vs. smaller vocabulary). We found that children with a larger vocabulary at 21 months had an increase in their pointing with words toward unfamiliar objects as well as in their total amount of words, whereas for children with smaller vocabularies we did not find differences in relation to their familiarization with objects. We discuss these findings in terms of a social-pragmatic use of pointing gestures.
Keywords: gesture; pointing; familiarity; individual differences

An Alternative to Mapping a Word onto a Concept in Language Acquisition: Pragmatic Frames - Rohlfing, Katharina; Wrede, Britta; Vollmer, Anna-Lisa; Oudeyer, Pierre-Yves (FRONTIERS IN PSYCHOLOGY)
The classic mapping metaphor posits that children learn a word by mapping it onto a concept of an object or event. However, we believe that a mapping metaphor cannot account for word learning, because even though children focus attention on objects, they do not necessarily remember the connection between the word and the referent unless it is framed pragmatically, that is, within a task. Our theoretical paper proposes an alternative mechanism for word learning. Our main premise is that word learning occurs as children accomplish a goal in cooperation with a partner. We follow Bruner's (1983) idea and further specify pragmatic frames as the learning units that drive language acquisition and cognitive development. These units consist of a sequence of actions and verbal behaviors that are co-constructed with a partner to achieve a joint goal. We elaborate on this alternative, offer some initial parametrizations of the concept, and embed it in current language learning approaches.
Keywords: language acquisition; pragmatics; infants' social learning; frames; learning and memory; developmental robotics

Preschoolers' engagement in social interaction with an autonomous robotic system - Lücking, Phillip; Rohlfing, Katharina; Wrede, Britta; Schilling, Malte (2016 Joint IEEE International Conference on Development and Learning and Epigenetic Robotics (ICDL-EpiRob))

Einstellungen zur Inklusion im Zusammenhang mit der Motivation für die Beschäftigung mit inklusionsspezifischen Fragestellungen bei Studentinnen und Studenten des Lehramts an Grundschulen. Vortrag auf der 4. Tagung der Gesellschaft für Empirische Bildungsforschung (GEBF) - Görel, Gamze; Hellmich, Frank; Schwab , Susanne

Rückmeldungen zu Leseprozessen in Elternhaus und Schule im Zusammenhang mit der Lesemotivation von Kindern im dritten und vierten Grundschuljahr. Vortrag auf der 4. Tagung der Gesellschaft für Empirische Bildungsforschung (GEBF) - Hellmich, Frank; Hoya, Fabian Karl

Einstellungen zum inklusiven Unterricht bei Lehrkräften als Voraussetzungen für inklusives Lernen in der Grundschule. Vortrag auf dem 25. Kongress der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE) - Görel, Gamze; Hellmich, Frank

Primary school children`s attitudes towards peers with special educational needs - Löper, Marwin Felix; Görel, Gamze; Pfahl, Rebecca; Hellmich, Frank

Primary school teachers` attitudes towards inclusion and their interest in inclusive teaching - Görel, Gamze; Hellmich, Frank

Leseleistungen von Kindern im Grundschulalter im Zusammenhang mit den Rückmeldungen ihrer Lehrerinnen und Lehrer im Leseunterricht der Grundschule – Ergebnisse aus einer Mehrebenenanalyse. Vortrag auf der 25. Jahrestagung „Profession und Disziplin – Grundschulpädagogik im Diskurs“ der Kommission Grundschulforschung und Pädagogik der Primarstufe (Sektion Schulpädagogik) der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE) - Hoya, Fabian Karl; Hellmich, Frank

Motivation und Einstellungen zur Inklusion bei deutschen und österreichischen Studentinnen und Studenten mit dem Studienschwerpunkt Grundschule – ein Vergleich. Vortrag auf der 25. Jahrestagung „Profession und Disziplin – Grundschulpädagogik im Diskurs“ der Kommission Grundschulforschung und Pädagogik der Primarstufe (Sektion Schulpädagogik) der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE) - Görel, Gamze; Hellmich, Frank; Schwab, Susanne

Bedingungsfaktoren für Einstellungen von Grundschulkindern gegenüber Peers mit sonderpädagogischem Förderbedarf. Vortrag auf der 25. Jahrestagung „Profession und Disziplin – Grundschulpädagogik im Diskurs“ der Kommission Grundschulforschung und Pädagogik der Primarstufe (Sektion Schulpädagogik) der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE) - Löper, Marwin Felix; Görel, Gamze; Pfahl, Rebecca; Hellmich, Frank

The role of pre-service teachers` attitudes towards inclusion for their motivation to engage in inclusive educational issues during their studies. Vortrag im Rahmen des Symposiums "Teachers' self-efficacy beliefs, attitudes and motivation to engage in inclusive education" (Chair: Marco Hessels). ECER 2016 (European Conference on Educational Research) - Hellmich, Frank; Görel, Gamze; Schwab, Susanne

The role of primary school students`perceptions of their parental and teachers` feedback for their reading motivation. Vortrag auf der ECER 2016 (European Conference on Educational Research). „Leading Education: The Distinct Contributions of Educational Research and Researchers" - Hoya, Fabian Karl; Hellmich, Frank

Kohäsion und soziales Kapital : Ausschließungsprozesse in der Sozialen Arbeit - Landhäußer, Sandra (Sozialmagazin)
Soziale Arbeit rückt im Zusammenhang mit der Thematisierung eines geringen gesellschaftlichen Zusammenhalts in den Vordergrund, wenn vermehrte Kohäsion mit der Aktivierung sozialen Kapitals erreicht werden soll. Vor diesem Hintergrund wird eine auf politischer Ebene prominente Version sozialen Kapitals sowie ihr Beitrag zur Erhöhung gesellschaftlichen Zusammenhalts genauer untersucht und auf seine Aussagekraft für die Soziale Arbeit hin befragt.

Evaluation der Reflexion: Wissenschaftliche Begleitung eines Projekts zur Überprüfung eines semesterübergreifenden Begleitangebots auf spezifische Aspekte der Persönlichkeit. - Seifert, Andreas; Balsam, Rebecca; Newig, Jens (Professionalisierung der Hochschuldidaktik)

Can 28-month-old children learn spatial prepositions robustly from pictures? Yes, when narrative input is provided. - Rohlfing, Katharina; Nachtigäller, Kerstin (Frontiers in Language Science)

Analysis of individual and systematic determinants regarding arithmetic skills of first graders. - Seifert, Andreas; Eilerts, Katja; Rinkens, Hans-Dieter (13th International Congress on Mathematical Education (ICME).)

Der Einfluss individueller und institutioneller Faktoren auf die Kompetenzeinschätzung von Studierenden im Praxissemester. - Festner, Dagmar; Gröschner, Alexander; Seifert, Andreas (4. Tagung der Gesellschaft der Empirischen Bildungsforschung (GEBF))

Analysekompetenz – ein mehrdimensionales Konstrukt. - Scholl, Daniel; Seifert, Andreas (DGFE-Kongress „Räume für Bildung. Räume der Bildung.“)

Global mobility policies, social positioning and boundary spanning work of expatriate managers - Mense-Petermann, Ursula; Spiegel, Anna

Verflochtene Mobilitäten und ihr Management. Mobilitätspraktiken von Expatriate-Managern und ihren ’trailing spouses’ im Auslandseinsatz - Spiegel, Anna; Mense-Petermann, Ursula (Österreichische Zeitschrift für Soziologie)
Der vorliegende Aufsatz behandelt die spezifischen Mobilitätsformen von Fach- und Führungskräften, die von ihren Unternehmen auf Zeit in eine ausländische Niederlassung entsandt werden, und die sie ermöglichende Mobilitäts- arbeit. Gezeigt wird, 1) dass es sich bei der Mobilität von Expatriates um komplexe verflochtene Mobilitäten handelt, die sich zu einer Hypermobilität verdichten, und 2) dass diese Hypermobilität konstitutiv auf die aktive Mobilitätsarbeit der mit reisenden Ehefrauen angewiesen ist. Damit wird deutlich, dass es sich hier um ein geschlechtsspezifisch strukturiertes Mobilitätsmanagement handelt. Die am Beispiel der Mobilität von Expatriates gewonnenen Befunde eröffnen auch neue theoretische Perspektiven für die Mobilitätsforschung insgesamt.

Rezension zu Brinkmann, Erika (Hrsg.): Rechtschreiben in der Diskussion. Schriftspracherwerb und Rechtschreibunterricht (= Beiträge zur Reform der Grundschule 140) Bad Langensalza: Beltz. 318 S. - Blachut, Alisa (Grundschulunterricht Deutsch)

Critical Theory of Communication: New Readings of Lukács, Adorno, Marcuse, Honneth and Habermas in the Age of the Internet - Fuchs, Christian

Reading Marx in the Information Age. A Media and Communication Studies Perspective on Capital Volume 1 - Fuchs, Christian

Sosyal Medya: Eleştirel Bir Giriş - Fuchs, Christian

Marx and the political economy of the media. Studies in critical social sciences. Volume 79

Marx in the age of digital capitalism. Studies in critical social sciences, Volume 80

马克思归来 (Marx is Back)

Lavoro digitale e imperialismo - Fuchs, Christian (Sinistrainrete)

Racism, Nationalism and Right-Wing Extremism Online: The Austrian Presidential Election 2016 on Facebook - Fuchs, Christian (Momentum Quarterly – Zeitschrift für sozialen Fortschritt (Journal for Societal Progress))

Georg Lukács as a Communications Scholar: Cultural and Digital Labour in the Context of Lukács’ Ontology of Social Being - Fuchs, Christian (Media, Culture & Society)

Baidu, Weibo and Renren: The Global Political Economy of Social Media in China - Fuchs, Christian (Asian Journal of Communication)

Dallas Smythe Today – The Audience Commodity, the Digital Labour Debate, Marxist Political Economy and Critical Theory. Prolegomena to a Digital Labour Theory of Value - Fuchs, Christian (Marx and the political economy of the media)

Critical Theory - Fuchs, Christian (International Encyclopedia of Communication Theory and Philosophy)

Critical Theory of Communication as Critical Sociology of Critique in the Age of Digital Capitalism: A Response to Jan Løhmann Stephensen's Rview Essay on Culture and Economy in the Age of Social Media - Fuchs, Christian (Conjunctions: Transdisciplinary Journal of Cultural Participation)

Henryk Grossmann 2.0: A Critique of Paul Mason’s Book “PostCapitalism: A Guide to Our Future“ - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)